Post-fire noxious weed mapping in Arapaho and Roosevelt national forests - Cheadle, Jessica, author; Baldvins, Tom, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2025)
This report documents the Colorado Natural Heritage Program's 2024 surveys of the Arapaho Roosevelt National Forest burn scars for noxious weeds. CNHP crews surveyed the burn scars of the 2020 fires from May 28, 2024, to September 6, 2024. The crews comprised of 2 groups of 6 seasonal technicians. All data were collected on tablets using ESRI Field Maps. Data were made available to USFS staff throughout the summer as data were collected. Crews mapped polygons of weed populations and recorded an estimate of number of individuals and percent cover of the weeds within the polygon. Crews would also take a photo of the weed in context of its landscape
Prepared for: U.S. Forest Service.
Keywords: Noxious weeds; Weeds; Vegetation surveys; burn-scars; mapping; Arapaho National Forest (Colo.); Roosevelt National Forest (Colo.); botany; climate change; conservation planning; ecology; vegetation mapping and classification; wetland condition assessments